2019
DOI: 10.1101/749721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional effects of chimeric antigen receptor co-receptor signaling domains in human Tregs

Abstract: Antigen-specific regulatory T cells (Tregs) engineered with chimeric antigen receptor (CARs) are a potent immunosuppressive cellular therapy in multiple disease models. To date the majority of CAR Treg studies employed second generation CARs, encoding a CD28 or 4-1BB co-receptor signaling domain and CD3z, but it was not known if this CAR design was optimal for Tregs.Using an HLA-A2-specific CAR platform and human Tregs, we compared ten CARs with different co-receptor signaling domains and systematically tested… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 94 publications
(101 reference statements)
6
17
3
Order By: Relevance
“…In line with a recent report (Dawson et al, 2020), we observed that the proliferative capacity of CAR-Tregs greatly varied between CD28 CAR-Tregs and 4-1BB CAR-Tregs. Indeed, 4-1BB CAR-Tregs had achieved 20-fold greater expansion than their CD28 counterparts at day 21.…”
Section: -1bb Induces Strong Tonic Signaling Which Enhances Treg Prsupporting
confidence: 93%
See 4 more Smart Citations
“…In line with a recent report (Dawson et al, 2020), we observed that the proliferative capacity of CAR-Tregs greatly varied between CD28 CAR-Tregs and 4-1BB CAR-Tregs. Indeed, 4-1BB CAR-Tregs had achieved 20-fold greater expansion than their CD28 counterparts at day 21.…”
Section: -1bb Induces Strong Tonic Signaling Which Enhances Treg Prsupporting
confidence: 93%
“…These results agreed with those for human chimerism in the blood, which was strongly inhibited by cotransfer of CAR-Tregs ( Figure 6D). Strikingly, circulating CAR-Tregs were readily detected on day 24 ( Figure 6D), far later than in previous reports (Dawson et al, 2020;Nowak et al, 2018). In our hands, a sizeable population of CAR-Tregs could be detected in the blood (median: 4.4 [0.2-9.1]% of circulating cells) as late as day 60-62 for CD28 CAR-Tregs, which was when mice were sacrificed ( Figure Supp 3A).…”
Section: Both 4-1bb Car-tregs and Cd28 Hla-a2 Car-tregs Are Efficientsupporting
confidence: 49%
See 3 more Smart Citations